22 Evaluation of a nurse led primary pci activation service. (5th October 2017) - Miller, T; Canning, A; McNeill, A; Ramsewak, A; Sharma, D; Shand, J; Davidavicius, G; McGlinchey, P; Peace, A
Abstract : Introduction: From the 15th September 2014 every citizen in Northern Ireland has 24/7 access to Cardiac Catheterisation for patients experiencing an acute STEMI or emergent PCI. In one of the 2 designated Primary Percutaneous Coronary Intervention (PPCI) enabled centres, registrar cover is not available, therefore the responsibility to activate the 24/7 PPCI Pathway was given to a senior cardiac nurse known as PPCI activator. AIM: To provide a safe and effective nurse led 24/7 PPCI service. Method: Consecutive calls received by the Activator from January 2015 to December 2015 were evaluated. An interventional cardiologist and senior PPCI activator retrospectively evaluated all case report files and ECGs. Each clinical decision made at the time of call was assessed and the diagnoses /outcomes were recorded. The total calls for the period Jan 2015 – Dec 2015 were recorded and continuous audit performed. Results: A total of 618 calls were received. Of this 416/618 (67%) were turned down. The nurse activators turned down 369/416 (89%)of the calls. The remaining 47/416 (11%) were turned down following discussion with the interventional cardiologist on call. On review all turn downs were deemed appropriate with a wide range of clinical diagnoses. Approximately 15% (58/416) of the referrals sent to the PPCI activator were actually discharged from the ER. Sepsis was diagnosed in 63/416 (15%) of cases. An acute coronary syndrome was ultimately diagnosed in 108/416 (25%) of cases. There were no inappropriate turn-downs by the PPCI activators. Conclusion: Nurse led decision-making in a PPCI pathway is a safe and effective way to manage referrals made for presumed STEMI. Work is required to improve ECG interpretation among those that refer to this pathway.